Politics of Counter-Memory in Turkey: Docudramatizing the Past as a Panacea for Official Discourses? - Nuran E. Işik (Conserveries Mémorielles)
The past of the Turkish Republic as well as the life of Mustafa Kemal Atatürk (the founder of the Republic) have always been narrated though memory rituals, speeches and official announcements, celebrations, movies and reports which created an ensemble of practices re-dramatizing the historical events and figures. Historical narratives reveal a discursive struggle among different voices and ideologies which constitute an important key to understand the projections about the future. The production of the docudrama Mustafa based on the idea of an alternative reading of the history of the Republic and Atatürk leads to the individualization of history. The documentary covers Atatürk’s life of so as to reveal some details or unknown anectodes about his private life which were never covered in such a genre. By doing this, the text defines itself a counter-discourse in opposite to official discourses which have been especially celebrating his military achievements and his role in establishing a nation state. The first part of the paper deals with the historical background whereby Turkish historiography employed symbolic forms of legitimation as modes of power and domination. As a response to hegemonic discourses, a critical/democratic historiography influenced works in popular history, exemplified by documentaries, biographies, and other genre. In the second half of the paper, Mustafa, as a discursive form of counter history is described. It is argued that the re-reading the docudrama offers an ample opportunity to understand major political cultural divisions in Turkey. Finally it is concluded what Mustafa does is to help us delineating the ideological lines of thought around essentialism and relativism which are both problematic to understand collective memory as well as national identity.